Harvesting the power of green synthesis: gold nanoparticles tailored for prostate cancer therapy - Oliveira, Marco (2024)
Biosynthetic gold nanoparticles (bAuNPs) present a promising avenue for enhancing biocompatibility and offering an economically and environmentally responsible alternative to traditional production methods, achieved through a reduction in the use of hazardous chemicals. While the potential of bAuNPs as anticancer agents has been explored, there is a limited body of research focusing on the crucial physicochemical conditions influencing bAuNP production. In this study, we aim to identify the optimal growth phase of Pseudomonas aeruginosa cultures that maximizes the redox potential and coordinates the formation of bAuNPs with increased efficiency. The investigation employs 2,6-dichlorophenolindophenol (DCIP) as a redox indicator. Simultaneously, we explore the impact of temperature, pH, and incubation duration on the biosynthesis of bAuNPs, with a specific emphasis on their potential application as antitumor agents. Characterization of the resulting bAuNPs is conducted using ATR-FT-IR, TEM, and UV-Vis spectroscopy. To gain insights into the anticancer potential of bAuNPs, an experimental model is employed, utilizing both non-neoplastic (HPEpiC) and neoplastic (PC3) epithelial cell lines. Notably, P. aeruginosa cultures at 9 h/OD600 = 1, combined with biosynthesis at pH 9.0 for 24 h at 58 ◦C, produce bAuNPs that exhibit smaller, more spherical, and less aggregated characteristics. Crucially, these nanoparticles demonstrate negligible effects on HPEpiC cells while significantly impacting PC3 cells, resulting in reduced viability, migration, and lower IL-6 levels. This research lays the groundwork for the development of more specialized, economical, and ecologically friendly treatment modalities.